Rights and obligations insights on the Family Code of selected married Filipino couples - De Leon, Rianna Glorinne G.; Bantang, Joanne R. (Quezon City University of the Philippines Diliman, 2025)
This study investigates the knowledge and lived experiences of selected Catholic Filipino spouses residing in Barangay U.P. Campus, Quezon City, regarding their rights and obligations under Title III of the Family Code of the Philippines. Using a mixed-methods approach, the research involved 52 middle-income spouses who took a paper-based exam to assess their understanding of legal provisions under the selected legal framework. A purposive subsample of 10 spouses was then interviewed to gain deeper insights into how these obligations are observed or challenged in their daily lives. Findings revealed that while a majority of spouses were familiar with general marital responsibilities, only 9 out of 52 passed the knowledge test, indicating gaps in legal comprehension. Interviews highlighted that most participants associated their understanding of marital obligations with religious teachings, personal experience, and family tradition rather than formal legal knowledge. Common best practices included open communication, financial cooperation, and mutual decision-making. However, challenges emerged in the areas of emotional intimacy, infidelity, conflict resolution, and taking initiative in fulfilling marital responsibilities. Several spouses also raised concerns about the limited accessibility of legal information and the lack of practical guidance on applying Title III in everyday situations. The study highlights the need to improve legal literacy among Filipino couples through targeted education and community-based initiatives to ensure that marital obligations are understood not only in principle but also in practice. Lastly, it recommends the integration of faith-based counseling and value formation programs to help couples align their lived experiences with both legal and spiritual dimensions of marriage.
In partial fulfillment for the Degree of Bachelor of Science in Home Economics
Thesis
Keywords: Marriage law -- Philippines; Husband and wife -- Philippines; Marriage -- Religious aspects -- Catholic Church; Rights and obligations; The Family Code